EEG in Panayiotopoulos Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The sequential changes in localization of EEG foci with age, and the relation between the clinical manifestations and EEG pattern in Panayiotopoulos syndrome (PS) were analyzed in a study of 76 children (37 boys and 39 girls) followed for>2 years at Tokyo Woman's Medical University, Japan.